Arlington Sustainability Action Plan, Vol. I. - Erickson, Jessica.; Lee, Benjamin.; Santimauro, Tara.; Seyhun, Sinan. (Tufts University. Tisch Library., 2018)
2005 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Sustainable Arlington.